Community-Based Digital Mental Health Modules and Mental Health Literacy Among Generation Z Students in Islamic Boarding Schools - Nahdiyatus Nur Fitriyah; Ahmad Guntur Alfianto; Miftakhul Ulfa (Universitas Ahmad Dahlan, 2026)
Background: Mental health is a growing issue in educational settings. Islamic boarding schools (pesantren) are educational environments based on a dormitory system. This creates mental health issues. Low mental health literacy among Islamic boarding school students (santri) is a significant issue in Islamic boarding schools (pesantren). Method: The study used a quasi-experimental, two-group pretest-posttest design with a sample of 78 students divided into intervention 38 studens and control groups 40 studens. The instrument used was the Mental Health Knowledge Questionnaire (MHKQ), Data analysis using paired t-tests and independent t-tests. Results: The results showed a significant increase in knowledge in the intervention group (p<0.05). There were significant differences between the intervention and control groups in indicators of basic concepts, causes, and treatment and management (p=0.000), but not in prevention (p=0.287). Conclusion: Digital modules are more effective than leaflets in improving mental health literacy among Islamic boarding school students, although they are not optimal for prevention.